A Case for and Against Ketogenic Diets in Athletes. Issue 1 (February 2017) - Kavalek, Matthew; Gannon, Ryan; Nelson, Mike T.
Abstract : ABSTRACT: THE SCIENTIFIC COMMUNITY GENERALLY ACKNOWLEDGES THE POTENTIAL BENEFITS OF A KETOGENIC DIET (KD) IN SOME CLINICAL AND/OR MEDICAL POPULATIONS. ALTHOUGH CURRENT EVIDENCE INDICATES ATHLETES RANGING FROM GYMNASTS TO ELITE ULTRAMARATHONERS MAY BENEFIT FROM A KD, MUCH DISAGREEMENT EXISTS REGARDING ITS SOUNDNESS IN ATHLETIC AND PHYSICAL PERFORMANCE SITUATIONS. THE FOLLOWING COLUMN WILL PRESENT A CASE FOR, AND AGAINST, THE USE OF KD IN ATHLETES. WE WANT TO HEAR FROM YOU. VISITNSCA-SCJ.COM TO WEIGH IN ON THE POINT/COUNTERPOINT QUICK POLL.